EXPLOSIVE POWER OF THE LOWER LIMBS IN FENCING AND TRACK AND FIELD ATHLETES - RADU, Ioana-Alexandra; GAMEN, Luisa Cristiana (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: Explosive power in the lower limbs is fundamental in fencing, influencing not only the performance, but also the overall dynamics of movements. Similarly, track and field events heavily rely on the strength and explosive capabilities of the lower limbs. Objective: The aim of the study was to compare the explosive power of the lower limbs between fencing and track and field athletes. Material and Methods: The study was conducted on 70 athletes (35 fencers and 35 track and field athletes) from Iasi, Romania, both males (37.1%) and females (62.9%), aged 13-14 years and 19-20 years. The instruments used to measure the explosive power in athletes were the Standing Long Jump (SLJ) Test and the Vertical Jump Test (Sargent Jump). Results: The analysis of the Standing Long Jump (SLJ) Test and the Vertical Jump Test (Sargent Jump) showed no statistically significant differences in the lower limb explosive power between the fencing and the track and field athletes for the first age group, but showed statistically significant differences in the second age group. Discussion: The Standing Long Jump (SLJ) Test and the Vertical Jump Test (Sargent Jump) act as benchmarks for younger athletes, allowing coaches to tailor training programs that cater to their specific need, thus enhancing their chances of success in both fencing and track and field. Conclusions: The Standing Long Jump Test and the Vertical Jump Test serve as a vital tool in the sports disciplines of athletics and track and field, providing essential metrics regarding explosive lower limb power.